ANALYSIS OF HEAVY VEHICLE PRODUCTIVITY ON THE TERBANGGI BESAR-KAYU AGUNG TOLL ROAD PROJECT KM 30+100 TO 30+500 - GALI PRIBADI; BILHAN GAMALIEL HARTANTO (CV KULTURA DIGITAL MEDIA, 2022)
Infrastructure projects, especially in flexible pavement work, are highly dependent on the use of heavy vehicles. This use is a crucial factor in supporting the success of asphalt road construction projects, where the production capacity of heavy vehicles plays a vital role in the progress of project implementation. Therefore, the calculation of production volume capacity analysis is important. The purpose of this study is to identify the production volume capacity of work on the construction of the Semarang-Demak Toll Road section 1C KM 35+400 to KM 36+400, including the capacity of asphalt finishers, dump trucks, pneumatic tire rollers, and tandem rollers. The method used is the volumetric method, which aims to calculate the volume and production capacity of heavy vehicles. The results of the analysis show that the calculation of the volume and productivity of heavy vehicles has been in accordance with the planned schedule.